Returns to overeducation: Returns to overeducation by College Major: Evidence from Turkey - (:unkn) unknown (Peter Lang AG, 2019)
This study uses the latest available 2017 Turkish Household Labor Force Surveys and analyzes the incidence of and returns to overeducation by college major, where overeducation indicates a position in which a worker's education level is one standard deviation above the average education level in her occupation. This chapter seeks to answer two questions: Which college majors yield to greater incidence of overeducation? Do earnings effects of being overeducated vary by college major? Two different specifications are estimated to answer these questions. First, separate logit models for male and female are estimated to see whether there are differences in the incidence of overeducation across majors. The findings indicate that there are substantial differences. Most of the fields that teach occupation-specific skills are observed not to yield high incidence of overeducation. In addition, it is found that likelihood of overeducation decreases by age both for male and female. Second, conditional earnings functions are estimated using quantile regressions to see whether earnings differences of being overeducated exist and vary by college major. The results reveal that there are earnings penalties of being overeducated and different college majors lead to strikingly different earnings losses of being overeducated. © Peter Lang AG 2019.
Keywords: College major; Overducation; Turkish labor market